A rare case of spontaneous tumor lysis syndrome in multiple myeloma - Louay Aldabain; Lyn Camire; David S. Weisman (Greater Baltimore Medical Center, 2020)
Spontaneous tumor lysis syndrome is an uncommon oncologic emergency. It occurs when a massive number of malignant cells release their contents to the blood stream without previous cancer treatment. TLS carries a mortality rate exceeding 15%. Because of the high mortality rate, the key to the management of TLS continues to be early recognition of high-risk patients and using prophylactic measures to prevent its occurrence. However, it remains difficult to completely eradicate TLS, as a small proportion of patients with aggressive tumors develop spontaneous TLS prior to receiving any therapy. We present a case of 58-year-old male with recently diagnosed multiple myeloma. He was found to have hyperkalemia, hyperphosphatemia, hyperuricemia, hypocalcemia, elevated LDH levels, and acute renal failure, fulfilling the criteria of clinical TLS. He was treated with rasburicase, continuous renal replacement therapy, and dexamethasone.